Burnout due to Workload: Qualitative Study of Finance Unit Employees at XYZ Hospital Semarang - Rheyna Salsabilla; Lucky Ade Sessiani; Abdul Wahib (IJIP : Indonesian Journal of Islamic Psychology, 2024)
Hospitals, as critical and high-intensity work environments, often place significant pressure on employees. High workloads, such as long working hours, huge responsibilities, and tight time demands, can be the main factors that cause burnout. The purpose of this study is to determine the level of burnout in the financial unit at XYZ Hospital, determine the determinant factors, and find effective strategies to cope with and prevent the negative impact of burnout. This study uses a qualitative approach as a research model. The research subjects/informants in the research were groups that focused on employees in the financial unit. There were four subjects with female staff. The technique used in data collection is interviews. Data analysis uses several stages, including data reduction and conclusion. The study results show that most employees experience high levels of burnout. A high level of emotional exhaustion indicates that employees feel drained of energy and cannot deal effectively with work pressure. High depersonalization indicates a cold attitude towards colleagues and clients. In addition, low self-esteem suggests a lack of satisfaction and a sense of accomplishment at work.